Precise timing when hitting falling balls - Brenner, Eli; Driesen, Ben; Smeets, Jeroen B. J. (Frontiers in Human Neuroscience, 2014)
People are extremely good at hitting falling balls with a baseball bat. Despite the ball’s constant acceleration, they have been reported to time hits with a standard deviation of only about 7ms. To examine how people achieve such precision, we compared performance when there were no added restrictions, with performance when looking with one eye, when vision was blurred, and when various parts of the ball’s trajectory were hidden from view. We also examined how the size of the ball and varying the height from which it was dropped influenced temporal precision. Temporal precision did not become worse when vision was blurred, when the ball was smaller, or when balls falling from different heights were randomly interleaved. The disadvantage of closing one eye did not exceed expectations from removing one of two independent estimates. Precision was higher for slower balls, but only if the ball being slower meant that one saw it longer before the hit. It was particularly important to see the ball while swinging the bat. Together, these findings suggest that people time their hits so precisely by using the changing elevation throughout the swing to adjust the bat’s movement to that of the ball.